Factors Associated with Death among COVID-19 Patients, Tak Province - สอนกอง กฤช (Journal of Health Science of Thailand, 2023)
The outbreak of the coronavirus 2019 disease (COVID-19) is the cause of pneumonia and death that affected the population globally. This retrospective analytical study aimed to study factors associated with death among patients with COVID-19 infection in Tak province. Data were collected from patients, s data center of the Tak Provincial Public Health Office during 1 June to 31 December 2021. The total of 15,442 cases were divided into two groups: the case study group of 258 people and the control group of 774 people through stratified random sampling. The data were analyzed by using multiple logistic regression. The results showed the factors that had a statistically significant association with death were: aged 65 years or older (ORadj = 10.00, 95%CI: 6.48-15.42, p<0.05); Burmese and stateless ethnicity (ORadj= 2.49, 95%CI: 1.56-3.98, p<0.05); chronic kidney disease (ORadj = 7.08, 95%CI: 2.02-24.81, p=0.002); having 1 chronic disease (ORadj= 3.77, 95%CI: 2.09-6.78, p<0.05); more than 1 chronic disease (ORadj = 7.26, 95%CI: 3.85-13.68, p<0.05); and dyspnea (ORadj = 6.77, 95%CI: 3.82-11.98, p<0.05). As for vaccination, it could reduce mortality from the COVID-19 disease: patients having 1 dose of the vaccine (ORadj = 0.11, 95%CI: 0.04-0.27, p<0.05), and having 2 doses (ORadj = 0.07, 95%CI: 0.02-0.27, p<0.05). In conclusion, the factors associated with the death were age 65 years and over, Burmese and statelessness ethnicity, chronic kidney disease, the number of concurrent chronic diseases, and dyspnea symptom. Moreover, vaccination could significantly reduce the risk of death of the patients. Therefore, the program design should focus on vaccination to cover such risk groups.